2016
DOI: 10.3171/2015.2.jns142856
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine use as an independent predictor of seizures after aneurysmal subarachnoid hemorrhage

Abstract: OBJECT Seizures are relatively common after aneurysmal subarachnoid hemorrhage (aSAH). Seizure prophylaxis is controversial and is often based on risk stratification; middle cerebral artery (MCA) aneurysms, associated intracerebral hemorrhage (ICH), poor neurological grade, increased clot thickness, and cerebral infarction are considered highest risk for seizures. The purpose of this study was to evaluate the impact of recent cocaine use on seizure incidence following aSAH. METHODS Prospectively collected dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
3
1
1
Order By: Relevance
“…In particular, drug abuse is an acknowledged risk factor for seizures regardless of aSAH [17]. In the setting of aSAH, it has been shown that cocaine use increases the risk of seizures during hospitalization [18]. In our study, individuals with drug abuse were more likely to present with SAO, but this association has failed to remain significant in multivariate analysis.…”
Section: Predictors Of Saocontrasting
confidence: 61%
“…In particular, drug abuse is an acknowledged risk factor for seizures regardless of aSAH [17]. In the setting of aSAH, it has been shown that cocaine use increases the risk of seizures during hospitalization [18]. In our study, individuals with drug abuse were more likely to present with SAO, but this association has failed to remain significant in multivariate analysis.…”
Section: Predictors Of Saocontrasting
confidence: 61%
“…It is significant that the three groups did not differ in the duration of responding, because it suggests that social contact does not influence the loss of circadian control of drug intake that might emerge during an extended binge of cocaine use. Rather, social contact influences the overall amount of cocaine consumed during a binge, which directly impacts the likelihood of an overdose related to stroke, seizure, or myocardial infarction (Chang, Kowalski, Carhuapoma, Tamargo, & Naval, 2016; Klonoff, Andrews, & Obana, 1989; Minor, Scott, Brown, & Winniford, 1991; Ritz & George, 1993). We previously reported that physical activity (i.e., wheel running) reduces cocaine intake during 23-hr test sessions by significantly decreasing the duration of responding and thus preserving the circadian control of behavior (Smith, Walker, Cole, & Lang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…One study further failed to find a difference in NIH Stroke Scale at the time of discharge between cocaine users and non-users [ 35 ]. Following stroke, cocaine users were at increased odds of having seizures compared to non-users (OR = 1.61) [ 32 , 36 , 38 ]. In cases of SAH, cocaine use was significantly associated with vasospasm (OR = 2.25) [ 20 , 24 , 29 , 36 , 46 ], with one study reporting a higher rate of aneurysm re-rupture in cocaine users (OR = 3.00) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“… Results from the risk of bias assessment [ 8 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. …”
Section: Figureunclassified